Engagement in the pre‐exposure prophylaxis (PrEP) cascade among a respondent‐driven sample of sexually active men who have sex with men and transgender women during early PrEP implementation in Zimbabwe. Issue 2 (11th February 2022) - Parmley, Lauren E.; Harris, Tiffany G.; Chingombe, Innocent; Mapingure, Munyaradzi; Mugurungi, Owen; Rogers, John H.; Gozhora, Perpetua; Wu, Yingfeng; Samba, Chesterfield; Musuka, Godfrey; Hakim, Avi J.
Abstract: Introduction: Zimbabwe is scaling up pre‐exposure prophylaxis (PrEP) for key populations, including men who have sex with men (MSM) and transgender women (TGW). To assess implementation and inform HIV programming, we evaluated gaps in PrEP awareness, uptake and use, and correlates of awareness and uptake among a sample of MSM, TGW and genderqueer individuals (GQ) in Harare and Bulawayo, Zimbabwe. Methods: Respondent‐driven sampling was used to recruit 1194 MSM and 344 TGW/GQ aged ≥18 to participate in a cross‐sectional survey assessing HIV‐related outcomes in 2019. Consenting participants completed a questionnaire on socio‐demographic information, sexual risk practices and engagement in HIV services and underwent HIV testing. Descriptive statistics were used to assess the PrEP cascade. Multiple logistic regression models were used to identify factors associated with PrEP awareness and uptake among HIV‐negative participants. Data were unweighted as the sample did not reach convergence on key estimates. Results: Among the 1167 HIV‐negative participants, most (79.2%) were MSM compared to TGW/GQ (20.8%). Median age was 24 years. Overall, 45.8% were aware of PrEP and of those, 31.3% had ever taken PrEP. Most (71.1%) reporting never taking PrEP were willing to start PrEP; the main reasons for never starting PrEP included not knowing where to access it (24.8%) and fearing side effects (20.4%). Among those who had ever taken PrEP, 74.9% had taken PrEP in the last 6 months; of these, 42.4% had taken PrEP the day of or day preceding the survey. Side effects represented the most common (59.5%) reason for discontinuing PrEP. MSM (adjusted odds ratio [aOR]: 2.5, 95% confidence interval [CI]: 1.8–3.6) and TGW/GQ in Harare (aOR: 3.1, 95% CI: 2.1–4.7), and TGW/GQ in Bulawayo (aOR: 2.4, 95% CI: 1.1–5.3) had higher awareness of PrEP than MSM in Bulawayo. Overall, TGW/GQ were more likely to have ever taken PrEP compared to MSM (aOR: 1.6, 95% CI: 1.01–2.4). Conclusions: Findings emphasize the need for tailored interventions to promote PrEP among key populations. As HIV programs in Zimbabwe continue to expand PrEP services, these data, including barriers to starting and continuing PrEP, can inform strategies to address gaps along the PrEP cascade.